THE INCLUSION OF LOCAL CULTURAL CONTENTS IN ENGLISH CLASSES: TEACHERS' PERCEPTIONS: TEACHERS' PERCEPTIONS - Sakinah Fitri Margianti (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2022)
This research is a descriptive study with a quantitative approach using a survey method. This research seeks to analyze and explain the perceptions of English teachers who teach Junior High School students toward the integration of local cultures in English Language Teaching descriptively and supported by percentage figures. The population of this research is all the English teachers of JHS (Junior High Schools) in Jambi City. The total number is 105 teachers. The sample in this study is the representative of English Junior High School teachers in Jambi city. Those are 40 teachers as the participants. The data in this research are collected by sharing a questionnaire on a piece of paper. Based on the findings, Language teachers normally think that local culture inclusion is really helpful to create a cheerful classroom, to make learners feel comfortable in the classroom and motivate them to persist with the class. In this point, learners’ local culture assists English teachers as they share some sense of interest and humor.